Potensi Pengembangan Skala Resiliensi Berbasis Falsafah Fiil Pesenggiri Masyarakat Lampung - Wahyudi, Amien; Setyowati, Aprilia; Kurniawan, Shopyan Jepri; Partini, Siti (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2022)
Humans live and develop cannot be separated from a culture. Humans can think, believe and feel according to their culture. The writing of this article was carried out with the aim of seeing the potential for developing a resilience scale based on the pasenggiri philosophyof the Lampung community. The writing of the paper is carried out by studying literature taken from various sources. The data obtained from this literature study are then described. Sources of data in writing this paper were obtained through books and journals obtained through the Google Schoolar database. The results of the study show that 1) In developing a psychological scale, the validity and reliability of the scale developed must pay attention to, 2) Piil Pesenggiri's philosophy contains the main teachings which which are mutually sustainable, including (i) pesenggiri (self-respect), (ii) bejuluk beadek (named with a title, (iii) mestiinyimah (having an open nature and paying respect to anyone), (iv) nengah nyappor (adaptability), ( v) sakai sambayan (containing, a form of caring, compassion, and generosity).